2021
DOI: 10.3390/brainsci11020233
|View full text |Cite
|
Sign up to set email alerts
|

Manic and Depressive Symptoms in Children Diagnosed with Noonan Syndrome

Abstract: Noonan syndrome (NS) is a dominant clinically variable and genetically heterogeneous developmental disorder caused by germ-line mutations encoding components of the Ras–MAPK signaling pathway. A few studies have investigated psychopathological features occurring in individuals with NS, although they were poorly analyzed. The aim of the present work is to investigate the psychopathological features in children and adolescents with NS focusing on depressive and hypo-manic symptoms. Thirty-seven subjects with mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…In adults, “only” a lower speed of information processing and social cognitive impairments have been demonstrated in case-control studies [ 10 , 11 ]. With respect to behavior and psychopathology, children with NSSDs tend to display more symptoms of attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) than do typically developing children, which is in line with deficits found in attention and social cognition [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. A higher risk of internalizing problems has been repeatedly described for both juveniles [ 13 , 14 , 20 , 21 ] and adults [ 10 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 89%
“…In adults, “only” a lower speed of information processing and social cognitive impairments have been demonstrated in case-control studies [ 10 , 11 ]. With respect to behavior and psychopathology, children with NSSDs tend to display more symptoms of attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) than do typically developing children, which is in line with deficits found in attention and social cognition [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. A higher risk of internalizing problems has been repeatedly described for both juveniles [ 13 , 14 , 20 , 21 ] and adults [ 10 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 89%
“…Psychological and psychosocial issues associated with NS may include increased clumsiness, stubbornness, and irritability and weaker social skills compared with unaffected siblings (1,97). Children with RASopathies, particularly NS, often display symptoms associated with attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD), including inattention, poor impulse control, and hyperactivity, although they may not always meet the stringent criteria necessary for an official diagnosis (12,13,15,17,97). Language impairments are more frequent in children with NS and are associated with a higher risk of reading and spelling difficulties (98).…”
Section: Hematologic/oncologicmentioning
confidence: 99%
“…Those with NS may also experience poor body image, selfesteem issues, anxiety, and depression (1,17). It has been suggested that some of these social issues may be linked to poor verbal development (95).…”
Section: Hematologic/oncologicmentioning
confidence: 99%
See 2 more Smart Citations